Pengaruh Latihan Resistensi Berbeda terhadap Variabel Fisik dan Performa Pelari 200 m - Ansam Khazaal Jabbar (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to identify effect of specific exercises with various forms of resistance among runners 200-meter short running events, through use of new methods and means in sports training that help improve some physical and motor abilities and level of performance. Materials and methods. The research method using experimental was used the experimental design of random selection equivalent groups with pre- and post-observation, Researcher selected sample intentionally, numbered (18) runners from Basrah Governorate clubs in 200-meter short-run event, in youth category (16 years old). The validity and reliability of instruments rely on extracted coefficient of self-truthfulness, and by test and retest to inform tests stability. Results: results of research showed that specific exercises for multi-form resistance have a positive effect on level of achievement among runners. Short distances, which were represented in physical variables and level of achievement, and that there were in variables of physical abilities and level of achievement, where they excelled. Conclusion. Concluded that experimental group that used proposed multi-form resistance training program over control group that used followed program. Benefiting from specific exercises for multi-form resistance 200-meter short sprint event. Attention to developing physical capabilities of performance stages resistance because their positive effect. Which makes these exercises preferable when training short-distance runners in future.